Analytical Detection of Gasoline and Kerosene Residues in Arson Fire Scenes Using Gas Chromatography Techniques (GC-FID) - أ. ابوبكر حسين محمد الطالب; أ. خديجة رمضان عبد السلام دخيلة (African Journal of Advanced Pure and Applied Sciences, 2026)
Background and Objective: Arson investigation is a complex field in forensics due to the extensive destruction that often leads to the loss of direct evidence related to accelerants. Given the widespread availability of flammable liquids, particularly gasoline and kerosene, this study aimed to develop and evaluate a reliable analytical protocol for detecting residues of these liquids in fire debris. The goal is to enhance the evidentiary capacity of forensic laboratories in identifying fire causes. Methodology: An experimental methodology was employed by preparing simulated combustion models on various substrates, including cotton fabric, wool fabric, cardboard, office wood, and automotive interior wood panels. Residual hydrocarbons were extracted using diethyl ether as a solvent, followed by concentration via slow evaporation. The extracts were subsequently analyzed using Gas Chromatography equipped with a Flame Ionization Detector (GC-FID). A systematic comparison was conducted between the chromatographic fingerprints of the burnt samples and the standard profiles of gasoline and kerosene, based on retention times (t_R) and the distribution patterns of aliphatic and aromatic compounds. Results: The results revealed distinct chromatographic peaks corresponding to gasoline residues across different samples, with retention times recorded between 5.274 and 14.657 minutes depending on the substrate. For kerosene, clear peaks were identified at retention times ranging from 11.509 to 16.366 minutes. A high degree of correlation was observed between the retention times of the burnt samples and the standard reference samples, with minor variations attributed to the substrate’s nature and thermal decomposition (pyrolysis) products. Conclusion: This study confirms that the integration of solvent extraction and GC-FID analysis provides an effective and sensitive method for detecting ignitable liquid residues (ILRs) in fire debris. The proposed protocol serves as a reliable forensic tool that supports investigative accuracy and strengthens the evidentiary value of analytical results in legal proceedings.